The Role of PARP Inhibitors in the Treatment of Gynecologic Malignancies - Reinbolt, Raquel E.; Hays, John L. (Frontiers in Oncology, 2013)
Gynecologic malignancies annually account for over 91,000 new cancer cases and approximately 28,000 deaths in the United States. Although there have been advancements in cytotoxic chemotherapies, there has not been significant improvement in overall survival in these patients. While targeted therapies have shown some benefit in many solid tumors, further development of these agents is needed for the treatment of gynecologic malignancies. Poly(ADP-ribose) polymerase (PARP) catalyzes the polyADP-ribosylation of proteins involved in DNA repair. Inhibitors of PARP were originally developed for cancers with homologous recombination deficiencies, such as those harboring mutations in BRCA1 or BRCA2 genes. However, pre-clinical research and clinical trials have suggested that the activity of PARP inhibitors is not limited to those with BRCA mutations. PARP inhibitors may have activity in cancers deficient in other DNA repair genes, signaling pathways that mitigate DNA repair, or in combination with DNA-damaging agents independent of DNA repair dysfunction. Currently there are seven different PARP inhibitors in clinical development for cancer. While there has been promising clinical activity for some of these agents, there are still significant unanswered questions regarding their use. Going forward, specific questions that must be answered include timing of therapy, use in combination with cytotoxic agents or as single-agent maintenance therapy, and whether there is a predictive biomarker that can be used with PARP inhibition. Even with large strides in the treatment of many gynecologic malignancies in recent years, it is imperative that we develop newer agents and methods to identify patients that may benefit from these compounds. The focus of this review will be on pre-clinical data, current clinical trials, and the future of PARP inhibitors in the treatment of ovarian, endometrial, and cervical cancer.